An optical coated glass cover plate impact resistant coating and method of making the same

CN122355597BActive Publication Date: 2026-10-30JIANGSU HAILIAN JINGSHENG OPTOELECTRONICS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610496226.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-04-15
Publication Date
2026-10-30
Estimated Expiration
2046-04-15

AI Technical Summary

Technical Problem

然而,此类复合结构往往因层间界面结合力弱、膜层应力匹配不当,导致在受到冲击时仍易出现层间剥离或膜层开裂,难以实现真正的协同增强效果

Benefits of technology

一、本发明采用“柔性抗冲击层+光学调节层+AF防指纹层”的多层复合结构,其中柔性抗冲击层采用纳米改性聚氨酯/丙烯酸树脂复合体系,能够通过弹性缓冲作用有效吸收冲击能量、阻断裂纹扩展;光学调节层为高折射率材料与低折射率材料交替叠加结构,在保证光学性能的同时提供结构支撑;AF防指纹层提供表面防护。通过各功能层的协同作用,实现了抗冲击与抗划伤性能的兼顾。经测试,采用本发明涂层的0.1mm~0.3mm厚度超薄玻璃,在16g钢球、50cm高度的落球测试中无破损,抗冲击强度≥0.8J/cm2,铅笔硬度可达9H,耐磨次数≥2000次,有效解决了现有技术中有机涂层硬度不足、无机涂层韧性差的矛盾。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1776066667520-000001
    Figure REF-OBJ-1776066667520-000001
Patent Text Reader

Abstract

The application discloses an optical coating glass cover plate impact-resistant coating and a preparation method thereof. The coating is a multilayer composite structure, and sequentially comprises a flexible impact-resistant layer, an optical adjustment layer and an AF anti-fingerprint layer from the inside to the outside of the substrate. The material of the flexible impact-resistant layer is a nano-modified polyurethane / acrylic resin composite system. The optical adjustment layer is an alternating superposition structure of high-refractive-index and low-refractive-index materials, the high-refractive-index material is selected from NB2O5, Ti3O5 or ZrO2, and the low-refractive-index material is selected from SiO2 or MgF2. The material of the AF anti-fingerprint layer is a perfluoropolyether material. The preparation method comprises substrate pretreatment, a wet coating process for preparing the flexible impact-resistant layer, ion source assisted vacuum evaporation coating for preparing the optical adjustment layer, resistance heating evaporation for preparing the AF anti-fingerprint layer, and process parameters are limited. The application has the advantages of synergistic effect of the multilayer structure, consideration of impact resistance, scratch resistance and excellent optical performance, high hardness, good wear resistance, controllable process, and suitability for the glass cover plate protection field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of coated glass, specifically, it relates to an impact-resistant coating for optical coated glass covers and its preparation method. Background Technology

[0002] With the rapid development of consumer electronics, automotive displays, and smart wearable devices, glass covers, as core protective components, not only need to possess excellent optical performance but also meet the requirements for high strength, impact resistance, and scratch resistance. This is especially true in applications such as foldable screens, AR / VR glasses, and automotive windshields, where even higher demands are placed on impact resistance.

[0003] Currently, the impact-resistant coatings for optical coated glass covers are mainly divided into three categories: inorganic coatings, organic coatings, and composite coatings. Although inorganic coatings have high hardness and wear resistance, they have poor toughness and are prone to cracking. When subjected to the impact of a falling ball, the coating may peel off or even the glass may break. Although organic coatings have good toughness and strong impact resistance, they lack hardness and have poor wear resistance. They are prone to scratches and aging after long-term use.

[0004] To combine the advantages of both, existing technologies have attempted to composite different functional layers, such as introducing flexible interlayers into hard coatings to alleviate stress. However, such composite structures often suffer from weak interlayer bonding and improper stress matching, leading to easy delamination or cracking under impact, making it difficult to achieve a true synergistic enhancement effect. Particularly in multilayer structures, the differences in physical properties and interlayer stress between functional layers have not been effectively addressed, limiting the improvement of the overall performance of composite coatings. Furthermore, most existing composite coatings do not simultaneously consider the optimization of optical performance, making it difficult to balance optical performance with the comprehensive performance requirements of impact and scratch resistance.

[0005] In terms of preparation process, existing mainstream processes such as vacuum evaporation and magnetron sputtering rely heavily on empirically set process parameters such as deposition temperature, vacuum degree, and evaporation current when applied to the preparation of impact-resistant coatings. This lack of precise matching for different film materials leads to unstable deposition rate, poor uniformity of film composition, and difficulty in controlling internal stress of the film, which in turn affects the impact resistance and consistency of the coating.

[0006] Therefore, there is an urgent need to develop an impact-resistant coating for optical coated glass covers and its preparation method that can achieve breakthroughs in interlayer bonding force, film stress matching, and precise control of process parameters, so as to take into account the comprehensive requirements of impact resistance, scratch resistance and optical performance and solve the shortcomings of existing technologies. Summary of the Invention

[0007] To address the aforementioned technical problems, this invention provides an impact-resistant coating for optical coated glass covers and a method for preparing the same.

[0008] To achieve the above objectives, the technical solution provided by the present invention is as follows: An optically coated glass cover plate impact-resistant coating, wherein the impact-resistant coating is a multi-layer composite structure, comprising, from the inside to the outside, a flexible impact-resistant layer, an optical adjustment layer, and an AF anti-fingerprint layer from the glass cover plate substrate; The flexible impact-resistant layer is made of a nano-modified polyurethane / acrylic resin composite system; the optical adjustment layer is a structure of alternating high-refractive-index and low-refractive-index materials, wherein the high-refractive-index material is selected from NB2O5, Ti3O5 or ZrO2, and the low-refractive-index material is selected from SiO2 or MgF2; and the AF anti-fingerprint layer is made of perfluoropolyether material.

[0009] Furthermore, a rigid reinforcement layer is provided between the flexible impact-resistant layer and the optical adjustment layer.

[0010] Furthermore, the hard reinforcement layer is a multilayer structure formed by alternating deposition of Si3N4 and SiO2.

[0011] Furthermore, another optical adjustment layer is provided on the surface of the glass cover substrate opposite to the surface where the flexible impact-resistant layer is located. This other optical adjustment layer is a structure of alternating superposition of high refractive index material and low refractive index material.

[0012] Furthermore, an AF anti-fingerprint layer is also provided on the surface of the glass cover substrate opposite to the surface where the flexible impact-resistant layer is located, located outside the other optical adjustment layer.

[0013] Preferably, the thickness of the flexible impact-resistant layer is 50~100nm.

[0014] Preferably, the thickness of the optical adjustment layer is 180~600nm.

[0015] Preferably, the thickness of the AF anti-fingerprint layer is 16~24nm.

[0016] This invention also provides a method for preparing an impact-resistant coating for an optically coated glass cover, comprising the following steps: (1) Substrate pretreatment: Clean the glass cover substrate; (2) Preparation of flexible impact-resistant layer: A wet coating process is used to coat the surface of the glass cover substrate with a nano-modified polyurethane / acrylic resin composite system, which is then cured to form a flexible impact-resistant layer. (3) Preparation of optical adjustment layer: Using vacuum evaporation coating process, high refractive index material and low refractive index material are alternately deposited under the assistance of ion source to form optical adjustment layer; (4) Preparation of AF anti-fingerprint layer: A perfluoropolyether material is deposited on the optical adjustment layer by resistance heating evaporation process to form AF anti-fingerprint layer.

[0017] Furthermore, when preparing the flexible impact-resistant layer, it is applied by spin coating, spraying, or dip coating, with a curing temperature of 80~120℃ and a curing time of 30~60min; when preparing the optical adjustment layer, the vacuum degree of the vacuum evaporation coating is 1.0×10⁻⁶. -3 ~3.0×10 -3 Pa; When preparing the AF anti-fingerprint layer, the current for resistance heating evaporation is 76~84A.

[0018] Compared with the prior art, the present invention has the following beneficial effects: I. This invention employs a multi-layered composite structure consisting of a flexible impact-resistant layer, an optical adjustment layer, and an anti-fingerprint layer. The flexible impact-resistant layer utilizes a nano-modified polyurethane / acrylic resin composite system, effectively absorbing impact energy and preventing crack propagation through elastic buffering. The optical adjustment layer is a structure of alternating high-refractive-index and low-refractive-index materials, providing structural support while ensuring optical performance. The anti-fingerprint layer provides surface protection. Through the synergistic effect of these functional layers, a balance between impact resistance and scratch resistance is achieved. Testing showed that ultra-thin glass with a coating of 0.1mm to 0.3mm thickness, using this invention's coating, remained undamaged after being dropped from a 16g steel ball at a height of 50cm, exhibiting an impact strength ≥0.8J / cm². 2 The pencil has a hardness of up to 9H and can withstand ≥2000 abrasion cycles, effectively solving the contradiction between insufficient hardness of organic coatings and poor toughness of inorganic coatings in existing technologies.

[0019] II. This invention achieves superior optical performance by employing an alternating superposition structure of NB2O5 / Ti3O5 / ZrO2 and SiO2 / MgF2 in the optical adjustment layer, combined with precise control of the thickness of each layer. The single-sided coating exhibits a transmittance ≥95% in the 420~680nm wavelength range, while the double-sided coating achieves a transmittance ≥98%, reflectance ≤1.5%, and haze ≤0.5%. While achieving high transmittance and low reflectance, it does not affect the display effect of the glass cover, meeting the stringent optical performance requirements of high-end optical display scenarios such as foldable screens, AR / VR glasses, and automotive displays. This overcomes the technical shortcomings of existing impact-resistant coatings that struggle to balance optical performance.

[0020] Third, the preparation method of this invention employs differentiated film deposition processes tailored to the characteristics of different film materials. The flexible impact-resistant layer utilizes wet coating to avoid the thermal decomposition of polymer materials under vacuum evaporation conditions, ensuring film integrity and performance stability. The optical adjustment layer and AF anti-fingerprint layer are deposited using vacuum evaporation, and through ion source assistance and precise current control, stable deposition rate, uniform film composition, and controllable internal stress are achieved. This process is simple in steps and has clearly defined parameters, avoiding problems such as unstable deposition rate and uneven film composition caused by improper parameter matching in existing processes. It has good mass production feasibility and process consistency, and can be widely used in various scenarios such as mobile phone cover plates, foldable screens, automotive display glass, and optical instrument lens cover plates, demonstrating strong practicality. Detailed Implementation

[0021] The specific embodiments are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. Unless otherwise specified, the raw materials and reagents used in the examples are commercially available.

[0022] The following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Although the invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the invention without departing from the spirit and scope of the invention, and all such modifications and substitutions should be covered within the scope of the claims of the invention. Example 1

[0023] An optically coated glass cover plate with an impact-resistant coating comprises, from the inside to the outside, a flexible impact-resistant layer, an optical adjustment layer, and an AF anti-fingerprint layer.

[0024] The flexible impact-resistant layer is made of a nano-modified polyurethane / acrylic resin composite system with a thickness of 75 nm.

[0025] The optical adjustment layer is a structure of alternating high-refractive-index and low-refractive-index materials, specifically NB2O5 layer and SiO2 layer, with a total thickness of 390nm, of which the NB2O5 layer is 130nm thick and the SiO2 layer is 260nm thick.

[0026] The AF anti-fingerprint layer is made of perfluoropolyether and has a thickness of 20nm.

[0027] The method for preparing the impact-resistant coating of the aforementioned optically coated glass cover is as follows: (1) Substrate pretreatment: The glass cover substrate is ultrasonically cleaned for 10 minutes at a temperature of 50°C. (2) Preparation of flexible impact-resistant layer: After the substrate pretreatment is completed, a nano-modified polyurethane / acrylic resin composite system is coated on the surface of the glass cover substrate by spin coating process. After coating, it is placed in a 100℃ oven for curing for 45 min to form a flexible impact-resistant layer with a thickness of 75nm. (3) Preparation of the optical adjustment layer: After the flexible impact-resistant layer is prepared, NB2O5 and SiO2 are alternately deposited under the assistance of an ion source using a vacuum evaporation electron gun deposition process to form the optical adjustment layer. The vacuum degree is 2.0 × 10⁻⁶. -3 Pa, in which the NB2O5 layer is 130nm thick, the SiO2 layer is 260nm thick, and the total thickness is 390nm; (4) Preparation of AF anti-fingerprint layer: After the optical adjustment layer is prepared, a perfluoropolyether material is deposited on the optical adjustment layer by resistance heating evaporation process to form AF anti-fingerprint layer. The process conditions are 80A current and 20nm thickness. Example 2

[0028] An optically coated glass cover plate with an impact-resistant coating comprises, from the inside to the outside, a flexible impact-resistant layer, an optical adjustment layer, and an AF anti-fingerprint layer.

[0029] The flexible impact-resistant layer is made of a nano-modified polyurethane / acrylic resin composite system with a thickness of 50 nm.

[0030] The optical adjustment layer is a structure of alternating high-refractive-index and low-refractive-index materials, specifically Ti3O5 and MgF2 layers, with a total thickness of 180 nm, of which the thickness of the Ti3O5 layer is 90 nm and the thickness of the MgF2 layer is 90 nm.

[0031] The AF anti-fingerprint layer is made of perfluoropolyether and has a thickness of 16nm.

[0032] The method for preparing the impact-resistant coating of the aforementioned optically coated glass cover is as follows: (1) Substrate pretreatment: The glass cover substrate is ultrasonically cleaned for 10 minutes at a temperature of 50°C. (2) Preparation of flexible impact-resistant layer: After the substrate pretreatment is completed, a nano-modified polyurethane / acrylic resin composite system is coated on the surface of the glass cover substrate by spraying process. After coating, it is placed in an 80℃ oven for 60 min to form a flexible impact-resistant layer with a thickness of 50nm. (3) Preparation of the optical adjustment layer: After the flexible impact-resistant layer is prepared, Ti3O5 and MgF2 are alternately deposited under the assistance of an ion source using a vacuum evaporation electron gun evaporation coating process to form the optical adjustment layer. The vacuum degree is 1.0 × 10⁻⁶. -3Pa, wherein the thickness of the Ti3O5 layer is 90 nm, the thickness of the MgF2 layer is 90 nm, and the total thickness is 180 nm; (4) Preparation of AF anti-fingerprint layer: After the optical adjustment layer is prepared, a perfluoropolyether material is deposited on the optical adjustment layer by resistance heating evaporation process to form AF anti-fingerprint layer. The process conditions are current 76A and thickness 16nm. Example 3

[0033] An optically coated glass cover plate with an impact-resistant coating comprises, from the inside to the outside, a flexible impact-resistant layer, a rigid reinforcement layer, an optical adjustment layer, and an AF anti-fingerprint layer.

[0034] The flexible impact-resistant layer is made of a nano-modified polyurethane / acrylic resin composite system with a thickness of 100 nm.

[0035] The hard reinforcement layer is a multilayer structure formed by alternating deposition of Si3N4 and SiO2, with a total thickness of 360nm. The Si3N4 layer and SiO2 layer are stacked alternately, with a single layer thickness of 40nm, for a total of 9 layers.

[0036] The optical adjustment layer is a structure of alternating high-refractive-index and low-refractive-index materials, specifically an alternating ZrO2 layer and a SiO2 layer, with a total thickness of 600 nm, of which the ZrO2 layer is 200 nm thick and the SiO2 layer is 400 nm thick.

[0037] The AF anti-fingerprint layer is made of perfluoropolyether and has a thickness of 24nm.

[0038] The method for preparing the impact-resistant coating of the aforementioned optically coated glass cover is as follows: (1) Substrate pretreatment: The glass cover substrate is ultrasonically cleaned for 10 minutes at a temperature of 50°C. (2) Preparation of flexible impact-resistant layer: After the substrate pretreatment is completed, the surface of the glass cover substrate is coated with nano-modified polyurethane / acrylic resin composite system by dip coating process. After coating, it is placed in a 120℃ oven for 30 min to form a flexible impact-resistant layer with a thickness of 100nm. (3) Preparation of hard reinforcement layer: After the flexible impact-resistant layer is prepared, Si3N4 and SiO2 are alternately deposited under the assistance of an ion source using a vacuum evaporation electron gun evaporation coating process to form a hard reinforcement layer with a vacuum degree of 3.0×10⁻⁶. -3 Pa, in which Si3N4 layer and SiO2 layer are stacked alternately, with a single layer thickness of 40nm, a total of 9 layers, and a total thickness of 360nm; (4) Preparation of the optical adjustment layer: After the hard reinforcement layer is prepared, ZrO2 and SiO2 are alternately deposited under the assistance of an ion source using a vacuum evaporation electron gun deposition process to form the optical adjustment layer. The vacuum degree is 3.0 × 10⁻⁶. -3 Pa, wherein the ZrO2 layer is 200 nm thick, the SiO2 layer is 400 nm thick, and the total thickness is 600 nm. (5) Preparation of AF anti-fingerprint layer: After the optical adjustment layer is prepared, a perfluoropolyether material is deposited on the optical adjustment layer by resistance heating evaporation process to form AF anti-fingerprint layer. The process conditions are current 84A and thickness 24nm. Example 4

[0039] An optically coated glass cover plate with an impact-resistant coating, wherein the first surface of the glass cover plate substrate includes, from the inside to the outside, a flexible impact-resistant layer, an optical adjustment layer and an AF anti-fingerprint layer, and another optical adjustment layer is disposed on the surface of the glass cover plate substrate opposite to the surface where the flexible impact-resistant layer is located, and an AF anti-fingerprint layer is disposed on the outside of the other optical adjustment layer.

[0040] The flexible impact-resistant layer on the first surface is made of a nano-modified polyurethane / acrylic resin composite system with a thickness of 80 nm.

[0041] The optical adjustment layer of the first surface is a structure of alternating high-refractive-index and low-refractive-index materials, specifically NB2O5 layer and SiO2 layer, with a total thickness of 300nm, of which NB2O5 layer is 100nm thick and SiO2 layer is 200nm thick.

[0042] The AF anti-fingerprint layer on the first surface is made of perfluoropolyether material with a thickness of 20nm.

[0043] The other optical adjustment layer on the opposite surface is a structure of alternating high-refractive-index and low-refractive-index materials, specifically NB2O5 layer and SiO2 layer, with a total thickness of 300nm, of which NB2O5 layer is 100nm thick and SiO2 layer is 200nm thick.

[0044] The AF anti-fingerprint layer on the opposite surface is made of perfluoropolyether material with a thickness of 20nm.

[0045] The method for preparing the impact-resistant coating of the aforementioned optically coated glass cover is as follows: (1) Substrate pretreatment: The glass cover substrate is ultrasonically cleaned for 10 minutes at a temperature of 50°C.

[0046] (2) Preparation of a flexible impact-resistant layer on the first surface: After the substrate pretreatment is completed, a spin coating process is used to coat the first surface of the glass cover substrate with a nano-modified polyurethane / acrylic resin composite system. After coating, the substrate is placed in a 100℃ oven for 45 minutes to form a flexible impact-resistant layer with a thickness of 80nm.

[0047] (3) Preparation of the optical adjustment layer of the first surface: After the flexible impact-resistant layer of the first surface is prepared, NB2O5 and SiO2 are alternately deposited under the assistance of an ion source using a vacuum evaporation electron gun evaporation coating process to form the optical adjustment layer of the first surface. The vacuum degree is 2.0 × 10⁻⁶. -3 Pa, wherein the NB2O5 layer is 100nm thick, the SiO2 layer is 200nm thick, and the total thickness is 300nm.

[0048] (4) Preparation of the AF anti-fingerprint layer on the first surface: After the optical adjustment layer on the first surface is prepared, a perfluoropolyether material is deposited on the optical adjustment layer on the first surface by resistance heating evaporation process to form the AF anti-fingerprint layer on the first surface. The process conditions are 80A current and 20nm thickness.

[0049] (5) Preparation of the optical adjustment layer on the opposite surface: After the preparation of each layer on the first surface, the glass cover substrate is flipped over. On the surface of the glass cover substrate opposite to the surface where the flexible impact-resistant layer is located, NB2O5 and SiO2 are alternately deposited using a vacuum evaporation electron gun evaporation coating process under the assistance of an ion source to form another optical adjustment layer. The vacuum degree is 2.0 × 10⁻⁶. - 3 Pa, wherein the NB2O5 layer is 100nm thick, the SiO2 layer is 200nm thick, and the total thickness is 300nm.

[0050] (6) Preparation of AF anti-fingerprint layer on opposite surface: After the optical adjustment layer on opposite surface is prepared, a perfluoropolyether material is deposited on the other optical adjustment layer by resistance heating evaporation process to form AF anti-fingerprint layer. The process conditions are current 80A and thickness 20nm.

[0051] Comparative Example 1 (without flexible impact-resistant layer) An optically coated glass cover with an impact-resistant coating comprises, from the inside to the outside, an optical adjustment layer and an AF anti-fingerprint layer on the glass cover substrate.

[0052] The optical adjustment layer is a structure of alternating high-refractive-index and low-refractive-index materials, specifically NB2O5 layer and SiO2 layer, with a total thickness of 390nm, of which NB2O5 layer is 130nm thick and SiO2 layer is 260nm thick.

[0053] The AF anti-fingerprint layer is made of perfluoropolyether and has a thickness of 20nm.

[0054] The method for preparing the impact-resistant coating of the aforementioned optically coated glass cover is as follows: (1) Substrate pretreatment: The glass cover substrate is ultrasonically cleaned for 10 minutes at a temperature of 50°C. (2) Preparation of the optical adjustment layer: After the substrate pretreatment is completed, NB2O5 and SiO2 are alternately deposited under the assistance of an ion source to form an optical adjustment layer using a vacuum evaporation electron gun evaporation coating process with a vacuum degree of 2.0×10⁻⁶. -3 Pa, in which the NB2O5 layer is 130nm thick, the SiO2 layer is 260nm thick, and the total thickness is 390nm; (3) Preparation of AF anti-fingerprint layer: After the optical adjustment layer is prepared, a perfluoropolyether material is deposited on the optical adjustment layer by resistance heating evaporation process to form AF anti-fingerprint layer. The process conditions are 80A current and 20nm thickness.

[0055] Comparative Example 2 (without optical adjustment layer) An optically coated glass cover plate with an impact-resistant coating comprises, from the inside to the outside, a flexible impact-resistant layer and an AF anti-fingerprint layer on the glass cover plate substrate.

[0056] The flexible impact-resistant layer is made of a nano-modified polyurethane / acrylic resin composite system with a thickness of 75 nm.

[0057] The AF anti-fingerprint layer is made of perfluoropolyether and has a thickness of 20nm.

[0058] The method for preparing the impact-resistant coating of the aforementioned optically coated glass cover is as follows: (1) Substrate pretreatment: The glass cover substrate is ultrasonically cleaned for 10 minutes at a temperature of 50°C. (2) Preparation of flexible impact-resistant layer: After the substrate pretreatment is completed, a nano-modified polyurethane / acrylic resin composite system is coated on the surface of the glass cover substrate by spin coating process. After coating, it is placed in a 100℃ oven for curing for 45 min to form a flexible impact-resistant layer with a thickness of 75nm. (3) Preparation of AF anti-fingerprint layer: After the flexible impact-resistant layer is prepared, a perfluoropolyether material is deposited on the flexible impact-resistant layer by resistance heating evaporation process to form AF anti-fingerprint layer. The process conditions are 80A current and 20nm thickness.

[0059] Comparative Example 3 (The optical adjustment layer is a non-alternating single-layer structure) An optically coated glass cover plate with an impact-resistant coating comprises, from the inside to the outside, a flexible impact-resistant layer, an optical adjustment layer, and an AF anti-fingerprint layer.

[0060] The flexible impact-resistant layer is made of a nano-modified polyurethane / acrylic resin composite system with a thickness of 75 nm.

[0061] The optical adjustment layer is a single-layer SiO2 layer with a thickness of 390nm.

[0062] The AF anti-fingerprint layer is made of perfluoropolyether and has a thickness of 20nm.

[0063] The method for preparing the impact-resistant coating of the aforementioned optically coated glass cover is as follows: (1) Substrate pretreatment: The glass cover substrate is ultrasonically cleaned for 10 minutes at a temperature of 50°C. (2) Preparation of flexible impact-resistant layer: After the substrate pretreatment is completed, a nano-modified polyurethane / acrylic resin composite system is coated on the surface of the glass cover substrate by spin coating process. After coating, it is placed in a 100℃ oven for curing for 45 min to form a flexible impact-resistant layer with a thickness of 75nm. (3) Preparation of the optical adjustment layer: After the flexible impact-resistant layer is prepared, a single layer of SiO2 is deposited using a vacuum evaporation electron gun evaporation coating process to form the optical adjustment layer. The vacuum degree is 2.0 × 10⁻⁶. -3 Pa, thickness 390nm; (4) Preparation of AF anti-fingerprint layer: After the optical adjustment layer is prepared, a perfluoropolyether material is deposited on the optical adjustment layer by resistance heating evaporation process to form AF anti-fingerprint layer. The process conditions are 80A current and 20nm thickness.

[0064] Comparative Example 4 (process parameters deviate from the scope of this invention) An optically coated glass cover plate with an impact-resistant coating comprises, from the inside to the outside, a flexible impact-resistant layer, an optical adjustment layer, and an AF anti-fingerprint layer.

[0065] The flexible impact-resistant layer is made of a nano-modified polyurethane / acrylic resin composite system with a thickness of 75 nm.

[0066] The optical adjustment layer is a structure of alternating high-refractive-index and low-refractive-index materials, specifically NB2O5 layer and SiO2 layer, with a total thickness of 390nm, of which the NB2O5 layer is 130nm thick and the SiO2 layer is 260nm thick.

[0067] The AF anti-fingerprint layer is made of perfluoropolyether and has a thickness of 20nm.

[0068] The method for preparing the impact-resistant coating of the aforementioned optically coated glass cover is as follows: (1) Substrate pretreatment: The glass cover substrate is ultrasonically cleaned for 10 minutes at a temperature of 50°C. (2) Preparation of flexible impact-resistant layer: After the substrate pretreatment is completed, a nano-modified polyurethane / acrylic resin composite system is coated on the surface of the glass cover substrate by spin coating process. After coating, it is placed in an oven at 150℃ for 45 min to form a flexible impact-resistant layer with a thickness of 75nm. (3) Preparation of the optical adjustment layer: After the flexible impact-resistant layer is prepared, NB2O5 and SiO2 are alternately deposited under the assistance of an ion source using a vacuum evaporation electron gun deposition process to form the optical adjustment layer. The vacuum degree is 2.0 × 10⁻⁶. -3 Pa, in which the NB2O5 layer is 130nm thick, the SiO2 layer is 260nm thick, and the total thickness is 390nm; (4) Preparation of AF anti-fingerprint layer: After the optical adjustment layer is prepared, a perfluoropolyether material is deposited on the optical adjustment layer by resistance heating evaporation process to form AF anti-fingerprint layer. The process conditions are 90A current and 20nm thickness.

[0069] Comparative Example 5 (Incorrect placement of the hard reinforcement layer) An optically coated glass cover plate with an impact-resistant coating comprises, from the inside to the outside, a flexible impact-resistant layer, an optical adjustment layer, a hard reinforcement layer, and an AF anti-fingerprint layer.

[0070] The flexible impact-resistant layer is made of a nano-modified polyurethane / acrylic resin composite system with a thickness of 100 nm.

[0071] The optical adjustment layer is a structure of alternating high-refractive-index and low-refractive-index materials, specifically an alternating ZrO2 layer and a SiO2 layer, with a total thickness of 600 nm, of which the ZrO2 layer is 200 nm thick and the SiO2 layer is 400 nm thick.

[0072] The hard reinforcement layer is a multilayer structure formed by alternating deposition of Si3N4 and SiO2, with a total thickness of 360nm. The Si3N4 layer and SiO2 layer are stacked alternately, with a single layer thickness of 40nm, for a total of 9 layers.

[0073] The AF anti-fingerprint layer is made of perfluoropolyether and has a thickness of 24nm.

[0074] The method for preparing the impact-resistant coating of the aforementioned optically coated glass cover is as follows: (1) Substrate pretreatment: The glass cover substrate is ultrasonically cleaned for 10 minutes at a temperature of 50°C. (2) Preparation of flexible impact-resistant layer: After the substrate pretreatment is completed, the surface of the glass cover substrate is coated with nano-modified polyurethane / acrylic resin composite system by dip coating process. After coating, it is placed in a 120℃ oven for 30 min to form a flexible impact-resistant layer with a thickness of 100nm. (3) Preparation of the optical adjustment layer: After the flexible impact-resistant layer is prepared, ZrO2 and SiO2 are alternately deposited under the assistance of an ion source using a vacuum evaporation electron gun deposition process to form the optical adjustment layer. The vacuum degree is 3.0 × 10⁻⁶. -3 Pa, wherein the ZrO2 layer is 200 nm thick, the SiO2 layer is 400 nm thick, and the total thickness is 600 nm. (4) Preparation of hard reinforcement layer: After the optical adjustment layer is prepared, Si3N4 and SiO2 are alternately deposited under the assistance of an ion source using a vacuum evaporation electron gun evaporation coating process to form a hard reinforcement layer with a vacuum degree of 3.0 × 10⁻⁶. -3 Pa, in which Si3N4 layer and SiO2 layer are stacked alternately, with a single layer thickness of 40nm, a total of 9 layers, and a total thickness of 360nm; (5) Preparation of AF anti-fingerprint layer: After the hard reinforcement layer is prepared, a perfluoropolyether material is deposited on the hard reinforcement layer by resistance heating evaporation process to form AF anti-fingerprint layer. The process conditions are current 84A and thickness 24nm.

[0075] Comparative Example 6 (AF anti-fingerprint layer thickness is below the lower limit) An optically coated glass cover plate with an impact-resistant coating comprises, from the inside to the outside, a flexible impact-resistant layer, an optical adjustment layer, and an AF anti-fingerprint layer.

[0076] The flexible impact-resistant layer is made of a nano-modified polyurethane / acrylic resin composite system with a thickness of 75 nm.

[0077] The optical adjustment layer is a structure of alternating high-refractive-index and low-refractive-index materials, specifically NB2O5 layer and SiO2 layer, with a total thickness of 390nm, of which the NB2O5 layer is 130nm thick and the SiO2 layer is 260nm thick.

[0078] The AF anti-fingerprint layer is made of perfluoropolyether and has a thickness of 10nm.

[0079] The method for preparing the impact-resistant coating of the aforementioned optically coated glass cover is as follows: (1) Substrate pretreatment: The glass cover substrate is ultrasonically cleaned for 10 minutes at a temperature of 50°C. (2) Preparation of flexible impact-resistant layer: After the substrate pretreatment is completed, a nano-modified polyurethane / acrylic resin composite system is coated on the surface of the glass cover substrate by spin coating process. After coating, it is placed in a 100℃ oven for curing for 45 min to form a flexible impact-resistant layer with a thickness of 75nm. (3) Preparation of the optical adjustment layer: After the flexible impact-resistant layer is prepared, NB2O5 and SiO2 are alternately deposited under the assistance of an ion source using a vacuum evaporation electron gun deposition process to form the optical adjustment layer. The vacuum degree is 2.0 × 10⁻⁶. -3 Pa, in which the NB2O5 layer is 130nm thick, the SiO2 layer is 260nm thick, and the total thickness is 390nm; (4) Preparation of AF anti-fingerprint layer: After the optical adjustment layer is prepared, a perfluoropolyether material is deposited on the optical adjustment layer by resistance heating evaporation process to form AF anti-fingerprint layer. The process conditions are 80A current and 10nm thickness.

[0080] Comparative Example 7 (AF anti-fingerprint layer thickness exceeds the upper limit) An optically coated glass cover plate with an impact-resistant coating comprises, from the inside to the outside, a flexible impact-resistant layer, an optical adjustment layer, and an AF anti-fingerprint layer.

[0081] The flexible impact-resistant layer is made of a nano-modified polyurethane / acrylic resin composite system with a thickness of 75 nm.

[0082] The optical adjustment layer is a structure of alternating high-refractive-index and low-refractive-index materials, specifically NB2O5 layer and SiO2 layer, with a total thickness of 390nm, of which the NB2O5 layer is 130nm thick and the SiO2 layer is 260nm thick.

[0083] The AF anti-fingerprint layer is made of perfluoropolyether and has a thickness of 30nm.

[0084] The method for preparing the impact-resistant coating of the aforementioned optically coated glass cover is as follows: (1) Substrate pretreatment: The glass cover substrate is ultrasonically cleaned for 10 minutes at a temperature of 50°C. (2) Preparation of flexible impact-resistant layer: After the substrate pretreatment is completed, a nano-modified polyurethane / acrylic resin composite system is coated on the surface of the glass cover substrate by spin coating process. After coating, it is placed in a 100℃ oven for curing for 45 min to form a flexible impact-resistant layer with a thickness of 75nm. (3) Preparation of the optical adjustment layer: After the flexible impact-resistant layer is prepared, NB2O5 and SiO2 are alternately deposited under the assistance of an ion source using a vacuum evaporation electron gun deposition process to form the optical adjustment layer. The vacuum degree is 2.0 × 10⁻⁶. -3 Pa, in which the NB2O5 layer is 130nm thick, the SiO2 layer is 260nm thick, and the total thickness is 390nm; (4) Preparation of AF anti-fingerprint layer: After the optical adjustment layer is prepared, a perfluoropolyether material is deposited on the optical adjustment layer by resistance heating evaporation process to form AF anti-fingerprint layer. The process conditions are 80A current and 30nm thickness.

[0085] Performance comparison tests were conducted on Examples 1-4 and Comparative Examples 1-7, and the test methods are as follows: I. Impact resistance test 1. Impact strength test (1) Test standard: Refer to GB / T 39814-2021 "Test method for impact resistance of ultra-thin glass" and the industry-standard falling ball impact test method.

[0086] (2) Testing equipment: Drop ball impact testing machine (equipped with steel ball release device) Steel ball: A standard steel ball with a diameter of 16g. Test bracket: used to fix the glass cover plate sample. (3) Test sample: Glass cover dimensions: 100mm × 100mm Glass thickness: 0.2mm (ultra-thin glass) Coating condition: The coating of this invention is applied to one or both sides. (4) Test steps: a. Place the glass cover sample horizontally on the test stand with the coating facing directly upwards; b. Place the 16g steel ball at a height of 50cm directly above the sample; c. Release the steel ball, allowing it to fall freely and impact the central region of the sample; d. Observe the sample for damage and record whether there is glass breakage or film peeling; e. For impact strength testing, the height of the sample is gradually increased, the height at which the sample breaks is recorded, and the impact strength is calculated.

[0087] (5) Formula for calculating impact strength: E = m × g × h, E: impact strength (J / cm²) 2 m: mass of the steel ball (kg), g: acceleration due to gravity (9.8 m / s²) 2 h: The height (m) at which the sample breaks. (6) Result determination: No breakage: The sample showed no glass breakage, no film peeling, and no cracks. Damage: The sample shows glass breakage or film peeling. Film peeling: the coating separates from the substrate. Film cracking: Cracks appear on the coating surface II. Scratch Resistance Test 1. Pencil hardness test (1) Test standard: Refer to GB / T 6739-2006 "Determination of paint film hardness by pencil method for paints and varnishes" and industry general standards.

[0088] (2) Testing equipment: Pencil hardness tester (750g load) Zhonghua brand high-grade drawing pencils (9H, 8H, 7H, 6H, 5H, 4H, 3H, 2H, H, F, HB, B, 2B, 3B, 4B, 5B, 6B) (3) Test steps: a. Sharpen the pencil by removing the wooden shaft, leaving about 5mm of lead exposed. Use sandpaper to smooth the end face of the lead, making the edges sharp. b. Place the pencil hardness tester on the sample surface, with the pencil at a 45° angle to the sample surface; c. Apply a load of 750g and push the pencil forward about 10mm at a speed of about 1mm / s; d. Observe the coating surface for scratches or damage; e. Repeat the test with pencils of different hardness until you find the pencil hardness level that just causes scratches on the coated surface.

[0089] (4) Result determination: The highest pencil hardness rating that ensures the coating surface is scratch-resistant is the pencil hardness of the coating. The higher the hardness rating, the better the scratch resistance. 2. Wear resistance test (1) Test standard: Refer to GB / T 1768-2006 "Determination of abrasion resistance of paints and varnishes by rotating rubber grinding wheel method" and industry general standards.

[0090] (2) Testing equipment: Abrasion testing machine (Taber type or equivalent equipment) Grinding wheel: CS-10 rubber grinding wheel Load: 500g (3) Test steps: a. Fix the sample on the turntable of the abrasion testing machine; b. Install the CS-10 rubber grinding wheel and apply a 500g load; c. Start the testing machine and rotate it at a speed of 60 r / min; d. Pause the test after every 500 rotations and observe the wear on the coating surface; e. Record the number of rotations when the coating surface shows obvious wear (exposing the substrate or peeling off the film).

[0091] (4) Result determination: The higher the wear resistance cycle, the better the wear resistance performance; a wear resistance cycle of ≥2000 cycles is considered excellent. III. Optical Performance Testing 1. Light transmittance test (1) Test standard: Refer to GB / T 2680-2021 "Determination of visible light transmittance, direct solar transmittance, total solar transmittance, ultraviolet transmittance and related window glass parameters of architectural glass" and industry general standards.

[0092] (2) Testing equipment: Ultraviolet-visible spectrophotometer (wavelength range 200~800nm) Integrating ball attachment (3) Test steps: a. Clean the sample thoroughly, ensuring the surface is free of dust and oil; b. Place the sample into the sample chamber of the spectrophotometer; c. Set the wavelength range to 380~780nm (or 420~680nm). d. Using air as a reference, scan the transmission spectrum of the sample; e. Record the average transmittance in the wavelength range of 420~680nm.

[0093] (4) Result determination: A single-sided coating with a light transmittance of ≥95% is considered superior, while a double-sided coating with a light transmittance of ≥98% is considered superior. 2. Reflectivity Test (1) Test standard: Refer to GB / T 2680-2021 "Determination of visible light transmittance, direct solar transmittance, total solar transmittance, ultraviolet transmittance and related window glass parameters of architectural glass" and industry general standards.

[0094] (2) Testing equipment: Ultraviolet-Vis spectrophotometer (with reflectance accessory) Integrating ball attachment (3) Test steps: a. Clean the sample thoroughly, ensuring the surface is free of dust and oil; b. Place the sample into the spectrophotometer sample chamber with the coating facing the incident light; c. Set the wavelength range to 380~780nm (or 420~680nm). d. Using a standard white board as a reference, scan the reflectance spectrum of the sample; e. Record the average reflectance in the wavelength range of 420~680nm.

[0095] (4) Result determination: A reflectivity of ≤1.5% is preferred; the lower the reflectivity, the better the anti-reflection performance. 3. Haze Test (1) Testing standards: Refer to GB / T 2410-2008 "Determination of light transmittance and haze of transparent plastics" and industry general standards.

[0096] (2) Testing equipment: Haze meter (such as BYK Haze-Gard or equivalent) (3) Test steps: a. Clean the sample thoroughly, ensuring the surface is free of dust and oil; b. Place the sample into the sample chamber of the haze meter; c. Perform a haze test according to the equipment operating instructions; d. Record the haze value of the sample.

[0097] (4) Result determination: A haze of ≤0.5% is considered excellent; the lower the haze, the better the transparency. IV. Anti-fingerprint performance test 1. Water droplet angle test (1) Test standard: Refer to GB / T 30693-2014 "Measurement of contact angle between plastic film and water" and industry general standards.

[0098] (2) Testing equipment: Contact angle measuring instrument (such as optical contact angle measuring instrument) (3) Test steps: a. Clean the sample thoroughly, ensuring the surface is free of dust and oil; b. Fix the sample on the sample stage of the contact angle measuring instrument; c. Use a microsyringe to drop 2 μL of deionized water onto the sample surface; d. Take images of the water droplets using an optical system and measure the contact angle between the water droplets and the sample surface using software; e. Repeat the test 5 times at different locations on the sample surface and take the average value.

[0099] (4) Result determination: A water droplet angle of ≥110° indicates good fingerprint resistance; the higher the water droplet angle, the better the hydrophobic and oleophobic properties. 2. Fingerprint Residue Test (1) Testing standard: Refer to the industry-standard fingerprint residue evaluation method.

[0100] (2) Testing equipment: Artificial fingerprint simulator (optional) Standard fingerprint oil (3) Test steps: a. Clean the sample thoroughly, ensuring the surface is free of dust and oil; b. Press your finger onto the standard fingerprint oil to evenly coat your fingertip; c. Gently press your finger, which has fingerprint oil on it, onto the sample surface and hold for 3 seconds; d. Observe the fingerprint residue under natural light or standard light source; e. Gently wipe with a lint-free cloth and observe how easily the fingerprints are removed.

[0101] (4) Result determination: No residue: fingerprints are almost invisible or can be completely removed with a gentle wipe. Slight residue: Fingerprints are faintly visible and can be removed by wiping. Obvious residue: Fingerprints are clearly visible and remain even after wiping. The test results are shown in the table below: Analysis of the table data yields the following: I. Verification of the Necessity of Flexible Impact-Resistant Layer By comparing Comparative Example 1 with Example 1, the necessity of the flexible impact-resistant layer can be clearly verified. Comparative Example 1, without the flexible impact-resistant layer, exhibited a 57% decrease in impact resistance compared to Example 1, resulting in glass breakage during the drop ball test. Simultaneously, the pencil hardness decreased by three levels, and the number of abrasion resistance cycles decreased by 29%. This comparative result fully demonstrates that the flexible impact-resistant layer, employing a nano-modified polyurethane / acrylic resin composite system, can effectively absorb impact energy and prevent crack propagation through elastic buffering, while also providing buffer support for the upper optical adjustment layer, indirectly improving scratch resistance. The absence of this layer leads to a sharp decline in impact resistance, and scratch resistance is also significantly affected.

[0102] II. Verification of the Necessity of the Optical Adjustment Layer By comparing Comparative Example 2 with Example 1, the necessity of the optical adjustment layer can be clearly verified. Comparative Example 2, which does not have an optical adjustment layer, has a 7.2% decrease in transmittance, a 6.6% increase in reflectivity, and a 0.8 percentage point increase in haze, resulting in severely degraded optical performance that cannot meet the requirements of high-end display scenarios.

[0103] It is worth noting that the impact resistance of Comparative Example 2 is basically the same as that of Example 1, indicating that the optical adjustment layer mainly contributes to the optical performance and complements the flexible impact-resistant layer without interfering with each other. This result verifies the rationality of the "flexible layer + optical layer" synergistic design, that is, the flexible layer is responsible for impact resistance, and the optical layer is responsible for optical optimization, with each performing its own function and working synergistically to enhance efficiency.

[0104] III. Verification of the superiority of alternating high and low refractive index structures By comparing Comparative Example 3 with Example 1, the superiority of the alternating high- and low-refractive-index structure can be clearly verified. Comparative Example 3 uses a single layer of SiO2 as the optical adjustment layer, resulting in a 4.2% decrease in transmittance, a 4.1% increase in reflectance, and a 0.4% increase in haze. This comparative result demonstrates that the alternating superposition structure of high- and low-refractive-index materials can achieve anti-reflection and anti-reflection effects over a wide wavelength range through optical interference effects, which is unattainable with a single-layer dielectric film. This patent employs an alternating superposition structure of NB2O5 / Ti3O5 / ZrO2 and SiO2 / MgF2, achieving excellent transmittance and low reflectance, fully demonstrating the optical optimization effect of this structure.

[0105] IV. Key Verification of the Location of the Hard Reinforcement Layer By comparing Comparative Example 5 with Example 3, the criticality of the hard reinforcement layer's location can be clearly verified. In Comparative Example 5, the hard reinforcement layer was placed between the optical adjustment layer and the AF anti-fingerprint layer. Its impact resistance decreased by 39%, the film cracked during the drop ball test, the pencil hardness decreased by two levels, the number of abrasion resistance cycles decreased by 45%, while the light transmittance decreased by 3.5% and the reflectivity increased by 0.9%. This comparative result proves that only when the hard reinforcement layer is located between the flexible impact-resistant layer and the optical adjustment layer can it effectively absorb the impact energy transmitted by the flexible layer, provide stable support for the optical layer, and prevent stress concentration leading to cracking. If the hard layer is placed outside the optical layer, it cannot form an effective synergistic reinforcement mechanism with the flexible layer. Furthermore, the optical properties of the hard layer will interfere with the anti-reflection and anti-transmittance effects of the optical adjustment layer, leading to deterioration of optical performance.

[0106] V. Verification of the Critical Significance of the Thickness Range of the AF Anti-Fingerprint Layer By comparing Comparative Examples 6 and 7 with Example 1, the critical significance of the AF layer thickness range of 16~24nm can be clearly verified.

[0107] In Comparative Example 6, the AF layer thickness was lower than the lower limit specified in this invention, resulting in a 9% decrease in the water droplet angle, noticeable fingerprint residue, a significant decrease in anti-fingerprint performance, and a 62% reduction in the number of abrasion resistance cycles. This indicates that when the AF layer is too thin, a continuous and dense anti-fouling layer cannot be formed, resulting in insufficient abrasion resistance and an inability to guarantee anti-fingerprint performance.

[0108] In Comparative Example 7, the AF layer thickness exceeded the upper limit specified in this invention, resulting in a 3.2% decrease in transmittance, a 0.9% increase in reflectance, and a 0.7 percentage point increase in haze. This indicates that an excessively thick AF layer can cause light scattering, affecting optical performance. Furthermore, an excessively thick AF layer can increase internal stress within the film, potentially impacting the overall stability of the coating.

[0109] Based on the test results of Comparative Example 6 and Comparative Example 7, it can be clearly concluded that the thickness of the AF anti-fingerprint layer can only be controlled within the range of 16~24nm to simultaneously achieve both anti-fingerprint performance and optical performance. Below the lower limit, the anti-fingerprint performance is insufficient, and above the upper limit, the optical performance deteriorates.

[0110] VI. Verification of the Critical Significance of Process Parameter Ranges By comparing Comparative Example 4 with Example 1, the critical significance of the parameter range of 80~120℃ for curing temperature of flexible impact-resistant layer and 76~84A for preparation current of AF layer can be clearly verified.

[0111] Comparative Example 4 showed that by increasing the curing temperature of the flexible impact-resistant layer to above the upper limit and the preparation current of the AF layer to above the upper limit, the impact resistance decreased by 45%, the pencil hardness decreased by 4 levels, the number of abrasion resistance cycles decreased by 62%, the water droplet angle decreased by 6%, and the anti-fingerprint performance was significantly degraded.

[0112] This comparison demonstrates that the curing temperature and current parameter ranges specified in this patent are not simple, conventional choices, but rather critical ranges optimized through extensive experimentation. Exceeding these ranges will lead to a decrease in the quality of the flexible layer film, reduced film uniformity, increased internal stress, and insufficient density of the AF layer, thereby affecting all performance indicators. The critical significance of this parameter range has been fully verified.

[0113] VII. Further Optimization and Verification of the Two-Sided Symmetrical Structure By comparing Example 4 with Example 1, the further optimization effect of the double-sided symmetrical structure can be verified. Example 4 has an optical adjustment layer and an AF anti-fingerprint layer on both sides of the glass cover substrate. Its double-sided light transmittance is increased by 3% compared with the single-sided structure, the reflectivity is reduced by 0.6 percentage points, the haze is maintained at an excellent level, and the impact resistance, scratch resistance, and anti-fingerprint performance are comparable to those of the single-sided structure.

[0114] This comparison demonstrates that adding an optical adjustment layer and an AF layer to the relative surface on top of a single-sided coating can further reduce reflectivity and increase light transmittance, meeting the needs of higher-end display scenarios, without negatively impacting shock and scratch resistance.

[0115] VIII. Conclusion on Overall Advantages Through a systematic analysis of the above seven sets of comparative examples, the following comprehensive conclusions can be drawn: 1. This patent adopts a three-layer composite structure of "flexible impact-resistant layer + optical adjustment layer + AF anti-fingerprint layer", with each functional layer having a clear division of labor and working synergistically. The flexible impact-resistant layer is responsible for absorbing impact energy and preventing crack propagation; the optical adjustment layer is responsible for achieving high light transmittance and low reflection; and the AF anti-fingerprint layer is responsible for providing anti-fouling and wear-resistant functions. The three work together to achieve a comprehensive balance of impact resistance, scratch resistance, and optical performance that cannot be achieved simultaneously by existing technologies.

[0116] 2. This patent features precise optimization of the basic structure. A rigid reinforcing layer is positioned between the flexible layer and the optical layer, effectively absorbing impact energy and providing support for the optical layer; the double-sided symmetrical structure further enhances optical performance. These optimizations have been verified through comparative experiments and demonstrate clear technical effectiveness.

[0117] 3. The AF layer thickness range and process parameter range defined in this patent have been verified through comparative studies and have clear critical significance; they are not simply conventional choices. Exceeding these ranges will lead to a significant deterioration in anti-fingerprint performance or optical performance, or affect the uniformity and stability of the film layer.

[0118] 4. The technical solution of this patent is significantly superior to the comparative example in all key performance indicators. The average impact strength, pencil hardness, abrasion resistance, light transmittance, reflectivity, and haze of the embodiment are all significantly better than the average level of the comparative example, fully demonstrating the significant superiority of the technical solution of this patent.

[0119] In summary, this patented technical solution achieves a synergistic improvement in impact resistance, scratch resistance, and optical performance through multi-layer composite structure design, precise material selection and thickness range limitation, and optimized process parameter matching. Performance comparison test results fully demonstrate that this patented technical solution significantly outperforms existing technologies and comparative examples in all key performance indicators, possessing significant advantages and outstanding substantive features.

[0120] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. It should not be considered that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, several simple deductions or substitutions can be made without departing from the concept of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the protection scope of the present invention.

Claims

1. An impact-resistant coating for an optically coated glass cover, characterized in that: The impact-resistant coating is a multi-layer composite structure, which includes, from the inside to the outside, a flexible impact-resistant layer, a hard reinforcement layer, an optical adjustment layer, and an AF anti-fingerprint layer from the glass cover substrate. The flexible impact-resistant layer is made of a nano-modified polyurethane / acrylic resin composite system with a thickness of 50-100 nm. The hard reinforcement layer is disposed between the flexible impact-resistant layer and the optical adjustment layer. It is a multilayer structure formed by alternating deposition of Si3N4 and SiO2, with a total thickness of 360nm and 9 layers. The optical adjustment layer is a structure of alternating high refractive index material and low refractive index material. The high refractive index material is selected from Nb2O5, Ti3O5 or ZrO2, and the low refractive index material is selected from SiO2 or MgF2. The thickness is 180-600 nm. The AF anti-fingerprint layer is made of perfluoropolyether material with a thickness of 16–24 nm.

2. The impact-resistant coating for optical coated glass covers according to claim 1, characterized in that: Another optical adjustment layer is provided on the surface of the glass cover substrate opposite to the surface where the flexible impact-resistant layer is located. This other optical adjustment layer is a structure of alternating superposition of high refractive index material and low refractive index material.

3. The impact-resistant coating for optical coated glass covers according to claim 2, characterized in that: An AF anti-fingerprint layer is also provided on the surface of the glass cover substrate opposite to the surface where the flexible impact-resistant layer is located, located outside the other optical adjustment layer.

4. A method for preparing an impact-resistant coating for an optically coated glass cover plate as described in any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Substrate pretreatment: Clean the glass cover substrate; (2) Preparation of flexible impact-resistant layer: A nano-modified polyurethane / acrylic resin composite system is coated on the surface of the glass cover substrate using a wet coating process, and a flexible impact-resistant layer is formed after curing. The coating is applied by spin coating, spraying or dip coating, with a curing temperature of 80-120℃ and a curing time of 30-60min. (3) Preparation of hard reinforcement layer: Si3N4 and SiO2 were alternately deposited using vacuum evaporation electron gun evaporation coating process with ion source assistance, and the vacuum degree was 3.0×10 -3 Pa, with a single layer thickness of 40nm, a total of 9 layers, and a total thickness of 360nm, forming a hard reinforcement layer; (4) Preparation of optical adjustment layer: Using vacuum evaporation deposition process, high refractive index material and low refractive index material are alternately deposited under the assistance of ion source to form optical adjustment layer. The vacuum degree is 1.0×10 -3 ~3.0×10 -3 Pa; (5) Preparation of AF anti-fingerprint layer: A perfluoropolyether material is deposited on the optical adjustment layer by resistance heating evaporation process to form AF anti-fingerprint layer. The resistance heating evaporation current is 76-84A.

Citation Information

Patent Citations

  • High-reliability UTG folding cover plate and preparation process thereof

    CN121672954A

  • Protective film, anti-fingerprint protective film, product with film and electronic product

    CN214491874U